- 85
- 50
- 95
- 58

So ab = 616

Given, (a^3 –b^3)/(a-b)^3 = 157/3

(a-b)*(a^2 + b^2 +ab)/(a-b)*(a^2 + b^2 -2ab) = 157/3

Let a^2 + b^2 =k

So (k+ab)/(k-2ab) = 157/3

3k + 3ab = 157k – 314ab

154k = 117ab = 317*616

k = 317*616/154 = 1268

As we know (a+b)^2 = (a^2 + b^2) + 2ab = k + 2ab = 1268 + 2*616

(a+b)^2 =2500 = 50^2

So a+b = 50

**a)** 1000+ Videos covering entire CAT syllabus**b)** 2 Live Classes (online) every week for doubt clarification**c)** Study Material & PDFs for practice and understanding**d)** 10 Mock Tests in the latest pattern**e)** Previous Year Questions solved on video